Environmental risk assessment of metformin and its transformation product guanylurea: II. Occurrence in surface waters of Europe and the United States and derivation of predicted no-effect concentrations. (February 2019) - Caldwell, Daniel J.; D'Aco, Vincent; Davidson, Todd; Kappler, Kelly; Murray-Smith, Richard J.; Owen, Stewart F.; Robinson, Paul F.; Simon-Hettich, Brigitte; Straub, Jürg Oliver; Tell, Joan
Abstract: Metformin (MET), CAS 1115–70–4 (Metformin hydrochloride), is an antidiabetic drug with high usage in North America and Europe and has become the subject of regulatory interest. A pharmaceutical industry working group investigated environmental risks of MET. Environmental fate and chronic effects data were collated across the industry for the present risk assessment. Predicted environmental concentrations (PECs) for MET were modeled for the USA and Europe using the P h ATE and GREAT-ER models, respectively. PECs were compared with measured environmental concentrations (MECs) for the USA and Europe. A predicted no effect concentration (PNEC) of 1 mg/L for MET was derived by deterministic procedures, applying an assessment factor of 10 to the lowest no observed effect concentration (i.e., 10 mg/L) from multiple chronic studies with algae, daphnids and fish. The PEC/PNEC and MEC/PNEC risk characterization ratios were <1, indicating no significant risk for MET with high Margins of Safety (MOS) of >868. MET is known to degrade during wastewater treatment to guanylurea (GUU, CAS 141–83–3), which we have shown to further degrade. There are no GUU toxicity data in the literature; hence, chronic studies for GUU were conducted to derive a PNEC of 0.16 mg/L. PECs were derived for GUU as for MET, plus MECs were retrieved from the literature. The PEC/PNEC and MEC/PNEC risk characterization ratios for GUU were also <1, with an MOS of >6.5. Based on standard risk assessment procedures for both MET and its transformation product GUU, there is no significant risk to aquatic life. Highlights: Previously unpublished chronic effects data for MET were collated for this study. A PNEC for MET was derived by deterministic procedures using these data. Chronic studies were conducted to derive a PNEC for GUU. PECs for MET and GUU were modeled and MECs were retrieved from literature. Risk characterization ratios were <1, indicating no significant risk for MET or GUU.